Academic distress among undergraduate students during COVID-19: the relevance of SES and help-seeking behaviors - Korn, Liat; Zigdon, Avi; Davidovitch, Nitza (Frontiers in Psychology, 2023)
Background: Academic distress was frequently reported following COVID-19. This study estimates academic distress among undergraduate students, characterizes its nature in relation to economic, social, and health indicators, and examines the level of request for help following mental distress. Students with higher levels of academic distress were expected to show lower socio-economic status, lower social connections, and lower well-being indices. Methods: A cross-sectional study based on a structured anonymous questionnaire delivered online to more than 1400 undergraduate students from one university in Israel (females, 66.7%). Results: Academic distress was reported by 27.1% of the sample. Students who reported academic distress were more likely to report stress, negative psycho-somatic symptoms, changes in weight since COVID-19, low self-esteem, depressive symptoms, higher COVID-19 concerns, and higher security situation concerns. Hierarchic logistic regression model showed that the probability of reporting academic distress was 2.567 times higher (p<.001 95% CI 1.702, 3.871) for those who reported lower family economic status before COVID-19, and 2.141 times higher (p=.004 95% CI 1.284, 3.572) for those who highly reported of depressive symptoms. In contrast, only 15.6% of those who reported academic distress sought help from academic authorities. Discussion: Significant associations with academic distress to health indices indicate that the self-reported distress was real and was highly related to adverse health measures. A comprehensive, collaborative model that integrates psychological, economic, and social aspects of intervention is required in times of crisis within academic institutions.